PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS V UPTD SD NEGERI 122365 PEMATANGSIANTAR - Geovani Malinda Sinaga; Minar T. Lumban Tobing; Jon Roi Tua Purba (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of the role playing learning model on the Pancasila education learning outcomes of class V UPTD students at SD Negeri 122365 Pematangsiantar. This research uses a quantitative research method with